Gestão de risco de incêndios: análise das políticas de proteção ao patrimônio arquivístico no Arquivo Público Mineiro (1990-2022) - Luiza Cristianne Ferreira Vieira Volpin (2022)
In the midst of disasters involving cultural institutions, it is necessary to expand studies and discussions on public policies for the preservation of archival heritage and the management of risks involving places for storing documents, with a special focus on archives. This is the proposed theme for this research. As a research problem, it is considered to identify whether public policies aimed at the preservation of cultural heritage (national and state) provide subsidies for the development of risk management actions against fire in archives and, also, how archival institutions carry out the operationalization of these policies for the protection of its collections. Among the agents of degradation pointed out by the Risk Management, it was decided to choose fire. In order to draw an overview of how these themes are treated today within the State of Minas Gerais, it was decided to elect an institution to serve as a base for studies, the Public Archive of Minas Gerais. The chronological cut of the research was also defined, from the 1990s to the present day. The implementation and management of security actions in places where documents are kept are necessary so that the preservation of the collections is guaranteed. Without these precautions, events that lead to the destruction of documentary heritage become more and more frequent, therefore, identifying and reflecting on policies for the protection of archival heritage and evaluating the operationalization of their regulations in the development of risk management actions - it was decided to elect an institution to serve as a base for studies, the Public Archive of Minas Gerais. The chronological cut of the research was also defined, from the 1990s to the present day. The implementation and management of security actions in places where documents are kept are necessary so that the preservation of the collections is guaranteed. Without these precautions, events that lead to the destruction of documentary heritage become more and more frequent, therefore, identifying and reflecting on policies for the protection of archival heritage and evaluating the operationalization of their regulations in the development of risk management actions – in the case of fires in archives - are the general objectives of the present study. Expectedthat the present research is a source of support and knowledge for institutions and professionals who work in document storage places, with the intention of improving the protection of cultural heritage in their custody.